MANAJEMEN SUMBER DAYA MANUSIA SEBAGAI INVESTASI STRATEGIS DALAM MEMBANGUN ORGANISASI BERKELANJUTAN (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Human Resource Management (HRM) plays a crucial role in determining organizational success and sustainability in an increasingly dynamic environment. However, HRM is often perceived merely as an administrative function rather than a long-term strategic investment. This article aims to analyze the role of Human Resource Management as a strategic investment in building sustainable organizations. The research method employed is a library research approach with qualitative analysis, conducted through a systematic review of books, academic journals, and relevant scholarly sources related to HRM, organizational strategy, and sustainability concepts. The findings indicate that strategically managed HRM contributes significantly to improving employee competencies, performance, and organizational commitment, as well as strengthening an adaptive and long-term-oriented organizational culture. Sustainable human resource development also enhances organizational competitiveness, internal stability, and the capacity to respond to environmental changes. These findings confirm that HRM should not be regarded as a cost, but as a strategic investment that directly influences organizational sustainability. Therefore, integrating HRM into organizational strategic planning is essential to achieve long-term sustainability and organizational resilience.